What will happen to Brazilian automotive subsidiaries after their parent companies make the transition to electric mobility?. (19th October 2011) - Proff, Heike
In the medium and long term, the automotive industry worldwide is expected to undergo radical discontinuous changes which will shake up a previously more or less stable industry. All serious automotive industry forecasts now anticipate that electric mobility will become established – in the industrialised countries at least – with fundamentally new vehicle concepts. Due to the long transition phase especially in the emerging markets, management of the 'ambidexterity' of optimising the existing technology and developing radically new ones is required. This article specifically examines the Brazilian automotive industry in the transition to electric mobility, i.e., the research question of what will happen to the Brazilian subsidiaries of international automotive companies after their parent companies make the transition to electric mobility. To answer this question, 30 top managers of automotive manufacturers, suppliers and industry associations as well as consultants and academics were interviewed in Brazil between January and March 2010.